Role of rubella in congenital malformations in India. - Chaturvedi, U. C. (Cambridge University Press, 1976)
In the present study rubella HI antibodies were determined in cases of congenital malformation and bad obstetric history to determine the role of rubella in such cases in India, as it has been reported to be rare in Japan in contrast to Western countries. The incidence of antibodies was statistically significant in cases of congenital eye, C.N.S., visceral and miscellaneous malformations and cases of spontaneous abortion and still-birth compared with controls of matching age groups. This is further supported by the demonstration of IgM antibodies in seven cases of congenital malformations and ten cases of spontaneous abortion. Our findings show that congenital rubella is not rare in India.